Solutions for Preventing Media Exposure to Vulnerable Groups and Marginalized Groups on Social Media - Sari, Elfira Maya; Mastanora, Refika (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
.Becoming Information access is very important for citizens to determine their own destiny, to participate in social and political life, as well as for development. However, the impact of the contemporary political economy of media in Indonesia has resulted in the premise of equal citizens' rights to media that still not being achieved. Business-powered media tend to prioritize the interests of the majority over the minority. Because the existence of the media remains important in society, it should be the key for the media industry to serve the interests of society, especially to provide for the needs of minority groups and vulnerable groups.